Репродуктивна здатність деяких видів роду Anemone L. в умовах культури - Pereboichuk, О.P.; Muzychuk, G.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The results of years of research especially seed and vegetative plant propagation of six species of the genus Anemone L. in conditions of culture are presented, which have different life forms and are promising for use in landscaping Polissya and Forest-Steppe of Ukraine. It established that ontomorphogenesis of monocarpic shoots of А. сanadensis, A. сylindrica, A. hupehensis, A. multifida, A. rivularis, A. sylvestris finishes by stable fruc ti fication. Plants characterize of high – 82–98 % (А. сanadensis, A. сylindrica, A. hupehensis, A. multifida) and middle – 51 % (A. rivularis) level of seed’s productivity realization, except A. sylvestris (7.5 %). The actual seed productivity is from 302.4 g/plant (A. сylindrica) to 1.5 g/plant (A. sylvestris). The main indicators of quality seed material are high, rarely – satisfactory. The coefficient of cloning of the researched species varies in a wide range (from 2 to 620 units) and depends on the species and age of plants, the methods of plant division. Of the four studied methods (cuttings vegetative rosette shoots with a piece of rhizome, root cuttings, dividing rhizomes, root sprouts) for all species, except A. rivularis with taproot, dominant or close to that signification are reproduction root cutting, effectiveness is in 10–20 times more than appropriate indices of other methods of cloning. Propagation by root sprouts is also productive for A. сanadensis.